2007
DOI: 10.1007/s10551-007-9400-x
|View full text |Cite
|
Sign up to set email alerts
|

Researching the Drivers of Socially Responsible Purchasing: A Cross-National Study of Supplier Diversity Initiatives

Abstract: drivers of CSR, Ethnic Minority Businesses, socially responsible purchasing, supplier diversity, supply chain,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(106 citation statements)
references
References 38 publications
1
98
0
6
Order By: Relevance
“…The broad range of topics includes analyses of the drivers of supplier diversity programs (Worthington et al, 2008); development of frameworks for analyzing CSR practices in global supply chains (Andersen and Skjoett-Larsen, 2009); and development of a sustainable purchasing portfolio model that reflects the ''triple bottom line'' (people, profit, planet) as the measure of sustainability performance (Pagell et al, 2010). While some of these studies suggested public procurement as an important factor (see, for example, Worthington et al, 2008), it remained largely unexamined.…”
Section: Csr In Supply Management Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…The broad range of topics includes analyses of the drivers of supplier diversity programs (Worthington et al, 2008); development of frameworks for analyzing CSR practices in global supply chains (Andersen and Skjoett-Larsen, 2009); and development of a sustainable purchasing portfolio model that reflects the ''triple bottom line'' (people, profit, planet) as the measure of sustainability performance (Pagell et al, 2010). While some of these studies suggested public procurement as an important factor (see, for example, Worthington et al, 2008), it remained largely unexamined.…”
Section: Csr In Supply Management Theorymentioning
confidence: 99%
“…The broad range of topics includes analyses of the drivers of supplier diversity programs (Worthington et al, 2008); development of frameworks for analyzing CSR practices in global supply chains (Andersen and Skjoett-Larsen, 2009); and development of a sustainable purchasing portfolio model that reflects the ''triple bottom line'' (people, profit, planet) as the measure of sustainability performance (Pagell et al, 2010). While some of these studies suggested public procurement as an important factor (see, for example, Worthington et al, 2008), it remained largely unexamined. The literature on supplier management and CSR is also relevant to the extent that it examines explicit attempts by firms to influence and manage the CSR of external entities (i.e., their suppliers, associated systems, and processes) Pedersen and Andersen, 2006;Reuter et al, 2010;Spence and Bourlakis, 2009).…”
Section: Csr In Supply Management Theorymentioning
confidence: 99%
“…The model is validated by case studies from the public and private sector. Another study aiming to provide a structured answer to the question of why organisations choose socially responsible practices was prepared by Worthington et al (2008). Based on information gathered from literature and case studies of US and UK firms, they analyse what drives the sample organisations to engage in developing supplier diversity initiatives.…”
Section: Literature On Motivations For Sustainable Procurementmentioning
confidence: 99%
“…DOI: 10.4018/978-1-4666-2119-0.ch002 Benefits may accrue in the future, providing further compelling reasons to adopt SD programmes. As an example, in the USA it has been projected that at current rates of demographic change, by 2045 minority groups may represent 46% of the total US population (Worthington, Ram, Boyal, & Shah, 2008) -representing a significant market share in the world's largest economy. Early engagement with these communities may allow an organisation to establish strong links with groups that may prove to be powerful markets in the near future.…”
Section: Outcome and Motivation For Sdmentioning
confidence: 99%